Storytelling Dolls Reduce Children's Anxiety During Hospitalization - Yunike; Jawiah; Khairun Nisa Febrianti (Journal of Applied Holistic Nursing Science, 2024)
Background: Typhoid fever or typhus abdominalis is an acute infectious disease caused by the bacteria Salmonella typhi. Typhoid fever in children can cause death in Indonesia. Typhoid disease has become an endemic public health threat because the spread of this disease increases the number of people infected and increases drug resistance, making prevention and treatment efforts more difficult. Often children who are treated in hospital experience hospitalization. One way to deal with hospitalization in children is by using distraction techniques. Objective: The aim of the case study is that researchers are able to carry out nursing implementation of distraction techniques: dolls to reduce anxiety in children with typhoid fever. Method: This research design uses a descriptive research design in the form of a case study. Data collection techniques include interviews, observation and using the SLKI checklist. Two respondents took cases, namely typhoid fever patients with anxiety at the Siti Fatimah Regional Hospital, Palembang. Results: Nursing Implementation of Distraction Technique: The doll showed a decrease in the level of anxiety in patients 1 and 2 with the results of decreased verbalization of confusion, decreased verbalization of worry about the condition at hand, decreased restless behavior, decreased tense behavior, improved concentration, improved sleep patterns, improved eye contact. Conclusion: The nursing implementation provided is in the form of distraction techniques: dolls are effective in reducing anxiety in children.